Analysis of Characteristics and Level of Efficiency on the Development of Organic Rice (Oryza sativa, L.) Farming Business in Boyolali Regency - suswadi suswadi; Agung Prasetyo (Journal of Biodiversity and Biotechnology, 2021)
Certified organic agriculture is a product that has competitiveness and opportunities for export. This study aims to determine and analyze the characteristics of farmers, the total cost and revenue and income of organic rice, ze the level of efficiency, and BEP (Break-Even Point) of certified organic rice farming. The sampling method used in this study was simple random sampling with a sample of 40 farmers calculated using the Slovin formula. The analysis used is: (1) the analysis of the mean score for the characteristics of the farmers, (2) the method of analyzing costs and revenues and farm income, and (3) the analysis of the efficiency of the farming business using the R/C (Return Cost Ratio) analysis method. The research location was determined purposively, namely Dlingo Village, Mojosongo District, Boyolali Regency. The results of the study concluded that: (1) The characteristics of organic farmers were that men are more involved than women, the age of organic farming business practicioners were above 50 years old, most of the farmers in Dlingo village have lived for more than 30 years, the main livelihood farmers in the agricultural sector. (2) Based on the total average cost for organic farming, the certified group has an average of Rp.20,495,000,- and The average revenue was Rp. 35,000,000,-. The income per planting season is Rp. 14.505.000,-. Organic certified farmer groups get an R/C ratio value of 1.7;  the R/C > 1 means that farming with certified organic systems is efficient. Rice farming with a certified organic system is profitable because the BEP value of production volume was 2,927 < farmers' production, while the BEP value for production price was 4,099 < selling price at the farmer level.Keywords: organic rice; income; efficiency;